2021
DOI: 10.1039/d0nj04035e
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of the carbon shell pore volume and core Pd size of Pd@hollow@C-X for the synthesis of H2O2

Abstract: Yolk–shell Pd@hollow@C-X (X = 1.5, 3.2, 4.5 and 6) catalysts with Pd as the core and porous carbon as the shell were prepared via the inverse microemulsion method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Similar results were reported by Wang 17 and Zhang. 18 Burch 19 and Thompson 20 showed that the presence of Pd 0 plays a key role in obtaining higher productivity of H 2 O 2 . In order to regulate and control the Pd nanoparticle size and Pd 0 /Pd 2+ ratio and to improve the selectivity and productivity of H 2 O 2 , halogen ions, metals, metal oxides and acids have been used to modify palladium-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Wang 17 and Zhang. 18 Burch 19 and Thompson 20 showed that the presence of Pd 0 plays a key role in obtaining higher productivity of H 2 O 2 . In order to regulate and control the Pd nanoparticle size and Pd 0 /Pd 2+ ratio and to improve the selectivity and productivity of H 2 O 2 , halogen ions, metals, metal oxides and acids have been used to modify palladium-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 (II) The poor solubility of reaction substrates H 2 and O 2 in the reaction medium results in a slow mass transfer rate of them to the active component Pd. 27 Better hydrophilicity is beneficial to enhance the dispersion of catalysts in the hydrophilic reaction medium and increases the contact probability of reaction substrates H 2 and O 2 with the catalyst, thus enlarging the contact area of catalysts and reactant molecules H 2 and O 2 . The higher dispersion of catalysts in the reaction medium can also enlarge its bed height, and in addition, the hydrophilicity of catalysts also influences the desorption ability of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…2,6,9,14 The Pd nanoparticle size, support property, and catalyst structure are the key factors for the catalytic activity and stability of Pd catalysts. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] At present, the structure of Pd catalysts mainly includes the supported type, tightly coated core-shell type, and hollow core-shell type. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The synthesis methods of traditional supported Pd catalysts are simple, but in the process of high-temperature heat treatment, Pd nanoparticles tend to aggregate into large size Pd particles due to their high surface energy which result in low dispersion and catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] At present, the structure of Pd catalysts mainly includes the supported type, tightly coated core-shell type, and hollow core-shell type. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The synthesis methods of traditional supported Pd catalysts are simple, but in the process of high-temperature heat treatment, Pd nanoparticles tend to aggregate into large size Pd particles due to their high surface energy which result in low dispersion and catalytic activity. At the same time, the direct synthesis of H 2 O 2 from H 2 and O 2 is a heterogeneous reaction process with strong mechanical stirring easily making Pd nanoparticles fall off from the support surface, thereby reducing the stability of supported Pd catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation